Analysis of Genetic Diversity on Medicinal Plants of Codonopsis javanica (Blume) Hook. f. using RAPD-PCR Technique Towards Conservation and Plant Breeding in Vietnam - Huyen, Pham Thanh; Long, Dinh Doan (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2017)
This study was subjected to assess the genetic diversity of Condonopsis javanica (Blume) Hook f. germplasm in Vietnam for the purposes of conservation and its breeding for planting expansion. Samples of 15 natural and cultivated accessions were collected throughout the country with two major areas of distribution in Northwest Highlands (Lao Cai, Ha Giang, Son La) and Western Highlands (Lam Dong, Kon Tum). DNA of 15 accessions were isolated and amplified by 12 arbitrary primers. A total of 106 RAPD-PCR loci were detected, among which 88 loci (83%) were polymorphic, whereas the other 18 (17%) were homogeneous for all the collected accessions. The cluster analysis showed that 15 accessions were divided into 2 obviously distinct groups. One consisted of 5 accessions collected in Northwest highlands, while the other consisted of 10 remaining accessions collected in West highlands. Thus, RAPD-PCR results indicated that there was abundant genetic diversity amongst natural and cultivated population of C. javanica in Vietnam and their genetic relationship appeared to be related to their geographic distance. Thus, germplasms at geographic distance should be subjected to the conservation and breeding programs of this medicinal plant species.  Keywords Condonopsis javanica, RAPD-PCR, genetic diversity, geographic distance References [1] Nguyễn Tiến Bân và nhiều người khác (2007). Sách đỏ Việt Nam (phần II - Thực vật), NXB Khoa học tự nhiên và công nghệ, tr 152 - 153 và 303-304. [2] Nguyễn Tập (2006). Danh lục Đỏ cây thuốc Việt Nam. Tạp chí Dược liệu, tập 11, số 3, tr. 97 - 105. [3] Đỗ Huy Bích và cộng sự (2003). Cây thuốc và động vật làm thuốc ở Việt Nam (Tập 1 + 2), NXB Khoa học và Kỹ thuật. [4] Sanghai-Maroof MA, KM Soliman, RA Jorgensen, RW Allard, Ribosomal DNA, Spacer-length polymorphisms in barly Mendelian inheritance, chromosomal location and population dynamics. Proc. Natl. Acad. Sci. USA., 81: 8014-8018. [5] Edwards K, Johnstone, Thompson C (1991) A simple and rapid method for the preparation of plant genomic DNA for PCR analysis. Nucleic Acids Res; 19(6): 1349.